Peningkatan Mutu Sekolah Dasar Melalui Total Quality Management - Hambali; Imami, Agus Sulthoni; Khoiriyah, Sri Wahyuni (AL MURABBI, 2022)
This study aims to determine the quality improvement of elementary schools through total quality management. This study uses a qualitative approach and the data collection technique used is the interview method. The result of the research is that Total Quality Management at SDN Kregenan 2 is one of the methods used to improve services to the community. Improving the quality of institutions there are three parts that must exist in the education, namely: (1) Input (input), (2) Process, and (3) Output. Efforts made at SDN Kregenan 2 in improving the quality of schools include focusing on customers, formulating a clear vision and mission, teamwork, and training all teachers to develop their potential.